EKSTRAKSI DAUN SIRSAK (ANNONA MURICATA L) MENGGUNAKAN PELARUT ETANOL - Galih Prihasetya Hermawan; Hendrawan Laksono; Indro Sumantri (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2013)
Soursop (Annona muricata L) is one of fruit that originated from Caribbean, middle America and south America. Acetogenins contain in the soursop especially in the leaves. Acetogenins is polyketides compound with structure straight carbon chain 30-32 that bounded with group 5-methyl-2-furanone. Furanone chain in the group of hydrofuranone have cytotoxic activity. One of the problem in the usage of soursop leaves extract is lack of efficiency of the solvent. This research have purpose to know affected variable and determined operation condition optimum in the extraction with maseration method of cytotoxic substance from soursop leaves. This research was engineered with factorial design method with 2 level and 4 independent variables which are drying material with and without drying, extraction time 1 and 2 days, samples mass 4 and 7 grams, fractination solvent etanol and n-hexane. The dependent variables are extraction’s volume solvent 200 ml, extraction temperature 28oC (room condition), and etanol solvent. The 4 independent variables give positive result / increases fenol level and the most affected variables are drying, samples mass, and extraction time. Optimum condition in the extraction process are 7 grams of weight, with drying process, and extraction time 2 days.